1978
DOI: 10.1111/j.1432-1033.1978.tb12682.x
|View full text |Cite
|
Sign up to set email alerts
|

ADP-Ribosylated Histone H1 from HeLa Cultures. Fundamental Differences to (ADP-Ribose)n-Histone H1 Conjugates Formed in vitro

Abstract: ADP-ribosylated histone H1 was isolated from intact HeLa cells grown for 24 h with [3H]-adenosine and compared with ADP-ribosylated histone H1 synthesized from [3H]NAD by isolated HeLa nuclei. Most (ADP-ribose),-histone H1 conjugates formed in vivo carried single ADP-ribose units, less than one fourth of the total ADP-ribose residues being in the form of oligomeric or polymeric chains. (ADP-ribose), linked to H1 in vivo was not released by neutral NH2OH to a significant extent. Alkali treatment (pH 10.5) liber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…In addition, histone H1 (32,33) and high mobility group proteins (34) are also often poly(ADP-ribosyl)ated. It has been demonstrated that poly(ADP-ribosyl)ation of histone results in opening up of the chromatin structure (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, histone H1 (32,33) and high mobility group proteins (34) are also often poly(ADP-ribosyl)ated. It has been demonstrated that poly(ADP-ribosyl)ation of histone results in opening up of the chromatin structure (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the apparent complexity of acceptor molecules observed in isolated nuclei may be lower in in situ nuclei, which is also observed in other modification reactions e.g. poly (ADP-ribosy1)ation [24] and phosphorylation [25]. This view is supported by the finding that treatment of isolated nuclei with detergents which may alter the structure and compartementalization of acceptor proteins and enzymes results in an increased activity of the transfer system.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, a chromatin-associated poly(ADPribose) polymerase can catalyse the transfer of the ADP-ribose moiety of NAD to acceptor proteins and the subsequent elongation of the protein-attached monomer to a polymer (Kawaichi et al, 1980). The enzyme has been shown to be capable of both auto-modification (Yoshihara et al, 1981 ;Kawaichi et al, 1981) and modification of histones H1, H2a, H2b and H3 in vitro (Jump et al, 1980;K awaichi et al, 1980) and H 1 in vivo (Ueda et al, 1975;Adamietz et al, 1978). It has also been implicated in cellular recovery from DNA damage (Durkacz et al, 1980;Durkacz et al, 1981 a, b;Sims et al, 1982) and may regulate DNA ligase activity (Creissen & Shall, 1982) as well as participating in shut-down of scheduled DNA synthesis after DNA damage (Edwards & Taylor, 1980).…”
Section: Discussionmentioning
confidence: 99%